Gut microbiota-mediated C-sulfonate metabolism impairs the bioavailability and anti-cholestatic efficacy of andrographolide - Dafu Tang; Wanyu Hu; Bingxuan Fu; Xiaojie Zhao; Guoquan You; Cong Xie; Hong Yu Wang; Xueni Guo; Qianbing Zhang; Zhongqiu Liu; Ling Ye (Gut Microbes, 2024)
Cholestatic liver injury results from the accumulation of toxic bile acids in the liver, presenting a therapeutic challenge with no effective treatment available to date. Andrographolide (AP) has exhibited potential as a treatment for cholestatic liver disease. However, its limited oral bioavailability poses a significant obstacle to harnessing its potent therapeutic properties and restricts its clinical utility. This limitation is potentially attributed to the involvement of gut microbiota in AP metabolism. In our study, employing pseudo-germ-free, germ-free and strain colonization animal models, along with 16S rRNA and shotgun metagenomic sequencing analysis, we elucidate the pivotal role played by gut microbiota in the C-sulfonate metabolism of AP, a process profoundly affecting its bioavailability and anti-cholestatic efficacy. Subsequent investigations pinpoint a specific enzyme, adenosine-5’-phosphosulfate (APS) reductase, predominantly produced by Desulfovibrio piger, which catalyzes the reduction of SO42- to HSO3−. HSO3− subsequently interacts with AP, targeting its C=C unsaturated double bond, resulting in the formation of the C-sulfonate metabolite, 14-deoxy-12(R)-sulfo andrographolide (APM). Inhibition of APS reductase leads to a notable enhancement in AP bioavailability and anti-cholestatic efficacy. Furthermore, employing RNA sequencing analysis and farnesoid X receptor (FXR) knockout mice, our findings suggest that AP may exert its anti-cholestatic effects by activating the FXR pathway to promote bile acid efflux. In summary, our study unveils the significant involvement of gut microbiota in the C-sulfonate metabolism of AP and highlights the potential benefits of inhibiting APS reductase to enhance its therapeutic effects. These discoveries provide valuable insights into enhancing the clinical applicability of AP as a promising treatment for cholestatic liver injury.